Onlay Mesh Repair for Abdominal Hernia; Do We Need a Paradigm Shift? (Medical Forum Monthly, 2021)
Objective: This study was done to compare the two techniques in the management of ventral hernia.Study Design: Comparative prospective studyPlace and Duration of Study: This study was conducted at unit 4 of the Department of Surgery, Liaquat University of Medical & Health Sciences, Jamshoro from August 2016 January 2017.Materials and Methods: A total of 105 patients, of both genders, aged above 13 years who were operated for VHR by onlay and sublay mesh repair, were enrolled. After randomization, Group A patients, VHR was done using onlay repair technique and in Group B, VHR was done by sublay repair technique. Data was collected on a performa and later analysed using SPSS 20.0.Results: Mean operation time was noted as 63.46+9.7 minutes in Group A in comparison to 72.28+9.5 minutes in Group B (p value < 0.0001). Mean duration of hospital stay in Group A was 5.98+1.27 days in comparison to 6.48+1.48 in Group B (p value = 0.0659).Overall, a total of 16 (30.2%) patients experienced complications in Group A in comparison to 7 (13.5%) in Group B (p value = 0.038). Recurrence was recorded in 6 (11.3%) patients of Group A while 3 (5.8%) in Group B (p value = 0.310). Seroma was noted to be the commonest complication, noted in 13 (24.5%) patients of Group A and 5 (9.6%) in Group B (p value = 0.043).Conclusion: Sublay mesh repair was found to be safe and effective technique for VHR in comparison to onlay mesh repair. Sublay mesh repair technique had less post operative complications. Considerentingsublay mesh repair safety and efficacy, longer operative time required can be neglected related to this technique.